(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigated the channel losses of a Digital Terrestrial Television Base Station (DTTBS) operating on 722 MHz in a Tropical Rain Forest, Sub Urban City of Akure, South West, Nigeria. The digital field strength values of the base station were measured at intervals of 1km along three selected routes around the station using a digital signal strength meter (Satlink WS-6936 model). A GPS receiver was used to monitor the line of sight with the station as reference and to log the geographic coordinates and heights of data points. A compact wireless weather station model N96FY was used for the measurement of surface meteorological parameters of Temperature, Atmospheric Pressure and Humidity of data locations whereas, the corresponding surface radio refractivity values along the routes were derived from the atmospheric components recorded. Data were collected during dry and wet seasons for comparative studies. Path loss along the routes for each of the seasons was calculated using Okumura-Hata model. Results for all the routes and seasons revealed that path losses were higher when using receiver antenna height of 1.5 m compared to that of 3.0 m. Also, path losses increase with distance in all the routes and seasons, however path losses were more significant during wet seasons compared to the dry seasons. In addition, the data obtained were used to revalidate existing path loss model for use in the study area. The overall findings of this work will be useful in Digital Terrestrial Television (DTTV) Industry for channel optimization and equipment design